Association between workaholism and quality of life in stricto sensu graduate professors in nursing - Taísa Vedoato; Danielli Rafaeli Candido Pedro; Maria José Quina Galdino; Patrícia Aroni; Cremilde Aparecida Trindade Radovanovic; Júlia Trevisan Martins; Maria do Carmo Fernandez Lourenço Haddad (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to investigate the association between workaholism and quality of life in stricto sensu graduate professors in Nursing. Methods: a cross-sectional study developed with a total of 333 professors working in the Graduate Programs of Brazilian public universities. Data collection took place in the second semester of 2018, using an electronic form containing a characterization questionnaire, the Dutch Work Addiction Scale and the World Health Organization Quality of Life Instrument-BREF. The data were analyzed by univariate and multiple logistic regression. Results: it was observed that 82.3% of the professors reported low general quality of life and 19.5%, high level of excessive work and 20.1% of compulsive work. Professors who worked compulsively and excessively were less likely to have a high quality of life in the overall, physical, psychological, social relations and environment domains (p<0.05). Conclusions: the high work demands that are characteristic of the stricto sensu professors' work process are directly associated with low quality of life.